RELATIONSHIP OF SOME MARKERS OF PSYCHO-EMOTIONAL STATE AND DEVELOPMENT OF SOMATIC PATHOLOGY IN THE PATIENTS WITH OCCUPATIONAL DISEASES - Данилов, Игорь Петрович; Дружилов, Сергей Александрович; Влах, Надежда Ивановна; Гугушвили, Максим Александрович (Medicine in Kuzbass, 2017)
Subject. The relationship of psycho-emotional state and somatic pathology in the patients with occupational diseases. Objective. The study of the relationship between professional disadaptation, alexithymia, emotional and personal behaviour in relation to his own health and the development of concomitant somatic pathology in the patients with occupational diseases. Methods. As the markers of a psycho-emotional state, professional disadaptation, alexithymia, the features of emotional and personal behaviour aimed at attitudes toward his own health were used. 72 patients with occupational diseases were examined, 40 of which had a somatic pathology. Results. There was no difference in the prevalence of somatic diseases among the patients with different levels of professional disadaptation and alexithymia. A health-improving lifestyle and a high level of motivation for health and a healthy lifestyle are higher among the patients who do not have somatic pathology. Field of application. Occupational medicine, occupational pathology, preventive medicine. Conclusions. The relationship between the emotional and personal attitude to health and a healthy lifestyle and the development of somatic diseases in the patients with occupational diseases has been revealed.